2D Covalent Organic Frameworks with an Incorporated Manganese Complex for Light Driven Carbon Dioxide Reduction. Issue 12 (2nd November 2021) - Wang, Denan; Streater, Daniel; Peng, Yun; Huang, Jier
Abstract: Covalent organic frameworks (COFs) have emerged as a novel class of crystalline porous photocatalytic materials due to their unique properties such as large surface area, tunable porosity, and rigid structure. In this work, we report the direct incorporation of a manganese CO2 molecular catalyst (MC) into COFs (Mn−TTA‐COF) and the evaluation of its capability as photocatalyst for visible light driven CO2 reduction to form CO. We found that the photocatalytic activity of Mn−TTA‐COF is quite low, which mainly results from the elimination of the CO ligand in the Mn MC upon light illumination, rendering its short duration in the catalytic reaction. While this is a central concern for the further use Mn−TTA‐COF as a CO2 reduction catalyst, we found that the stability and efficiency of Mn MC is largely enhanced after being incorporated into COFs with respect to its homogeneous version, suggesting the capability of COFs as heterogeneous platform to incorporate MC and improve the catalytic performance of MC. Moreover, transient absorption spectroscopic studies show that the intramolecular charge transfer lifetime of the Mn‐incorporated COF is longer than that in the parent COF, which suggests that charge separation (CS) may occur from the parent COF to the Mn moiety. These results together suggest that COFs may show promise as a platform for creating next‐generation photocatalysts with a built‐in photosensitizer and MC, which can facilitate CS and enhance the stability and efficiency of the incorporated MC. Abstract : Charge transfer : A Mn(CO3 )(BPy)Br (Bpy=2, 2′‐bipyridyl) molecular complex is incorporated into a TTA‐COF (Mn−TTA‐COF; COF=covalent organic framework; TTA=4, 4′, 4′′‐(1, 3, 5‐triazine‐2, 4, 6‐triyl) trianiline), which can catalyze visible light driven CO2 reduction to form CO with significantly enhanced stability and efficiency with respect to its homogenous version. Transient absorption spectroscopic studies demonstrate charge transfer from the parent TTA‐COF to the manganese moiety.